Towards transformative resilience: community, neighbourhood and system responses during the COVID-19 pandemic. (21st July 2021) - Rippon, Simon; Bagnall, Anne-Marie; Gamsu, Mark; South, Jane; Trigwell, Joanne; Southby, Kris; Warwick-Booth, Louise; Coan, Susan; Woodward, Jenny
ABSTRACT: Issues presented by COVID-19 to community resilience are located at individual, community and system level. In this paper, we reflect on WHO Europe propositions on what makes resilient communities, and explore how communities and systems with varying capacity have responded to the pandemic by absorbing and adapting to challenges. In our research, we are seeing local responses at all three levels, which challenge current assumptions about the respective roles of citizen, local voluntary sector and state. This paper presents opportunities and challenges to translating this reactive social movement into proactive resilience-transforming change in how local systems work in the future.